2013
DOI: 10.1021/bi401205n
|View full text |Cite
|
Sign up to set email alerts
|

New Paradigm for Allosteric Regulation of Escherichia coli Aspartate Transcarbamoylase

Abstract: For nearly 60 years, the ATP activation and the CTP inhibition of Escherichia coli aspartate transcarbamoylase (ATCase) has been the textbook example of allosteric regulation. We present kinetic data and five X-ray structures determined in the absence and presence of a Mg(2+) concentration within the physiological range. In the presence of 2 mM divalent cations (Mg(2+), Ca(2+), Zn(2+)), CTP does not significantly inhibit the enzyme, while the allosteric activation by ATP is enhanced. The data suggest that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 53 publications
(114 reference statements)
0
37
0
Order By: Relevance
“…4A). The enzymatic activity of ATCase is allosterically regulated by the binding of one or two nucleotides to each regulatory subunit, with purines (adenosine and guanosine bases) enhancing activity and pyrimidines (cytidine and thymidine bases) inhibiting activity (49).…”
Section: Ligand Binding Reveals Multimeric Allosteric Coupling: Asparmentioning
confidence: 99%
“…4A). The enzymatic activity of ATCase is allosterically regulated by the binding of one or two nucleotides to each regulatory subunit, with purines (adenosine and guanosine bases) enhancing activity and pyrimidines (cytidine and thymidine bases) inhibiting activity (49).…”
Section: Ligand Binding Reveals Multimeric Allosteric Coupling: Asparmentioning
confidence: 99%
“…A later study by Cockrell et al demonstrated the importance of Mg 2+ as a cation for the nucleotide effectors. 147 In this work, it was shown that although CTP on its own can inhibit the enzyme, activity is restored with addition of physiological levels of Mg 2+ . Instead, the highest degree of inhibition was observed with the combination of the pathway products CTP and UTP in the presence of Mg 2+ (Figure 10).…”
Section: Solution X-ray Scatteringmentioning
confidence: 84%
“…As noted by Cockrell et al , the predicted scattering of the PALA-bound structure with Mg 2+ -ATP (Figure 14, black dotted) is slightly greater than that of the structure with only PALA bound (Figure 14, black solid). 147 However, neither of the predicted curves describes the experimentally obtained scattering of PALA-bound ATCase in solution with (Figure 14, red) or without (Figure 14, orange) Mg 2+ -ATP.…”
Section: Solution X-ray Scatteringmentioning
confidence: 91%
See 2 more Smart Citations